SELEKSI BAHAN PUSTAKA DALAM PENGEMBANGAN KOLEKSI DI PERPUSTAKAAN AKPER KARYA BAKTI HUSADA YOGYAKARTA.pdf - Fitri Kartika Sari (Central Library of Universitas Sebelas Maret, 2017)
This research discuss about material library selection of collection development in Akper Karya Bakti Husada library. This research aims to know how the material library selection have been processed in Akper Karya Bakti Husada library. Methode that used in this research has result that material library selection in Akper Karya Bakti Husada library do taking down student and lectures suggestion